AI-Based English Learning Applications to Skyrocket Students’ English Morphological Awareness - Suadi, Suadi; Sahyoni; Siregar, Ayu Meita Puteri; Anggoro, Kiki Juli (SALEE: Study of Applied Linguistics and English Education, 2024)
This article investigated how AI-based English learning applications contribute to English morphological awareness. This study involved 62 participants of university students. A quantitative approach was employed. Data collection was conducted by distributing questionnaires via Google Forms. Participants completed three types of questionnaires; (1) students’ habits in using AI-based English learning platforms, (2) Students’ morphological awareness, and (3) compositional test where participants were asked to make sentences based on provided words. The results show that the majority of participants used AI-based English applications for learning English. Additionally, the majority of them said they understood morphology when utilizing the English language. Likewise, the significance value for students’ habit in using AI-based English learning applications and students’ English morphological awareness is 0.000 and the Pearson correlation is 0.464. This means there is a moderate and positive correlation between students' morphological awareness and their usage of AI-based English learning platforms. Ultimately, the majority of students demonstrated a positive degree of morphological skill in English in their compositional test responses using the provided English vocabulary.